Genetic analysis of DNA methylation and hydroxymethylation genes in Parkinson's disease - Shu, Li; Qin, Lixia; Min, Shishi; Pan, Hongxu; Zhong, Junfei; Guo, Jifeng; Sun, Qiying; Yan, Xinxiang; Chen, Chao; Tang, Beisha; Xu, Qian (Neurobiology of aging, 2019)
DNA methylation is an important regulatory mechanism of Parkinson's disease (PD). To investigate the relationship between DNA methylation and hydroxymethylation genes and PD, we performed gene-targeted sequencing using molecular inversion probes in a Chinese PD population. We sequenced 12 genes related to DNA methylation and hydroxymethylation in 1657 patients and 1394 control subjects. We conducted genewise association analyses of rare variants detected in the present study and identified the TET1 gene as important in PD (p = 0.0037738, 0.013, 0.019521 (b.collapse test, variable threshold test, and skat-o test, respectively; sex + age as covariates). However, no positive results were observed when conducting association analyses on common variants in these genes. We performed a comprehensive analysis of associations between variants of DNA methylation and hydroxymethylation genes and PD, resulting in determination that TET1 might play a role in PD. •A large Chinese PD cohort (1657 patients and 1394 controls) were included.•A comprehensive analysis on the 12 DNA methylation/hydroxymethylation genes in PD with target sequencing using molecular inversion probes (MIPs).•TET1 might play a role in PD.